Two new species of the genus Oryctopterus (Orthoptera: Stenopelmatidae: Oryctopinae) from India, with some notes on biology - Hiremath, S.R.; Prathapan, K.D. (European Journal of Taxonomy, 2021)
The genus Oryctopterus Karny, 1937 (Orthoptera, Stenopelmatidae, Oryctopinae) is reported from India for the first time and two new species, Ot. varuna sp. nov. and Ot. yeshwanthi sp. nov. are described. Male and female external genitalia of Ot. varuna sp. nov. and female genitalia of Ot. yeshwanthi sp. nov. are figured and described. Notes on seasonality, food habits and behavior of Ot. varuna sp. nov. are provided.